2015
DOI: 10.47811/bhj.08
|View full text |Cite
|
Sign up to set email alerts
|

Status of Thiamin deficiency in boarding school children from seven districts in Bhutan with previous history of peripheral neuropathy outbreaks: a cohort study

Abstract: Introduction: Peripheral neuropathy outbreaks have been a common occurrence amongst boarding schoolchildren from seven districts in Bhutan. Thiamin deficiency has always been suspected to be the cause but the status of the vitamin has never been established. This study aims to find the status of thiamin and dietary intake of micronutrients in boarding schoolchildren from seven districts with previous history of peripheral neuropathy outbreaks. Methods: Whole blood thiamin and dietary intake of micronutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This is further supported by the nutritional analysis which shows low intakes of all vitamin containing foods in the schools. Previous studies conducted among the boarding schools in Bhutan reported the lack of thiamine and cobalamin among the students [ 17 , 18 ]. The findings from this study suggests similar underlying nutritional deficiency in affected schools.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the nutritional analysis which shows low intakes of all vitamin containing foods in the schools. Previous studies conducted among the boarding schools in Bhutan reported the lack of thiamine and cobalamin among the students [ 17 , 18 ]. The findings from this study suggests similar underlying nutritional deficiency in affected schools.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of infantile beriberi occurred in exclusively breastfed infants of mothers who consumed thoroughly washed white rice and followed post‐partum dietary restrictions. A number of outbreaks of thiamine deficiency have been documented among boarding schoolchildren in Bhutan in recent years (Dzed et al 20152018).…”
Section: Risk Factors and Prevalence Of Thiamine Deficiencymentioning
confidence: 99%
“…A recent study from India reported that 32% of the healthy school children are deficient in vitamin B12 which was even more pronounced in the rural areas and in school children who had poor dietary intakes [10] . Bhutanese school children are also vulnerable to the deficiency of this vitamin as outbreaks of micronutrient deficiency diseases have been a common occurrence [11,12] . The causes of these outbreaks in the Bhutanese school children have been attributed to poor dietary intakes of micronutrient rich foods, including animal source foods [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Bhutanese school children are also vulnerable to the deficiency of this vitamin as outbreaks of micronutrient deficiency diseases have been a common occurrence [11,12] . The causes of these outbreaks in the Bhutanese school children have been attributed to poor dietary intakes of micronutrient rich foods, including animal source foods [11] . Therefore, it is very plausible that vitamin B12 could be very much deficient among the school children of Bhutan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation